Pathological investigations on theileriosis caused by theileria annulata in brown calves - Nazır Dumanlı; M. Kemal Çiftçi (Eurasian Journal of Veterinary Sciences)
This study was made to inestigate the macroscopical and microscopical changes in calves which died and were slaughtered compulsorily from experimental theileriosis. In this study four splenectomized calves aged 6 to 8 months were used.